Broadband Internet: An Information Superhighway to Sex Crime? - Bhuller, M.; Havnes, T.; Leuven, E.; Mogstad, M. (Review of Economic Studies, 2013)
Does internet use trigger sex crime? We use unique Norwegian data on crime and internet adoption to shed light on this question. A public program with limited funding rolled out broadband access points in 2000–2008, and provides plausibly exogenous variation in internet use. Our instrumental variables estimates show that internet use is associated with a substantial increase in both reports, charges and convictions of rape and other sex crimes. We present a conceptual framework that highlights three mechanisms for how internet use may affect reported sex crime, namely a reporting effect, a matching effect on potential offenders and victims, and a direct effect on sex crime propensity. To investigate the importance of these mechanisms, we use data on individual reporting behaviour, police investigations, and criminal charges and convictions. None of the analyses we perform suggest that the positive relationship between internet use and sex crime is driven by changes in reporting behaviour. Our findings suggest that the direct effect on sex crime propensity is positive and non-negligible, possibly as a result of increased consumption of pornography. Copyright 2013, Oxford University Press.